COMPARISON OF BIPOLAR AND MONOPOLAR CAUTRY USE IN TURP FOR TREATMENT OF ENLARGED PROSTATE - Ahmad, Mushtaq; Khan, Hazratullah; ullah, Amin; Masood, Iqra; Masood, Warda; Malik, Asif (Journal of Ayub Medical College Abbottabad, 2016)
Background: In recent years, bipolar Transurethral resection of prostate (TURP) has been increasingly being used by urologist instead of conventional monopolar TURP for the treatment of enlarge prostate. Bipolar TURP is considered to be more efficacious and has better clinical outcome in comparison with monopolar TURP. We compared both procedures to assess their clinical out-comes and efficacy by comparing their different parameters. Methods: This randomized control trial was conducted in the Institute of Kidney Diseases and Transplant Peshawar over 220 consecutive patients from Sep 2013 to Dec 2014. Patients were randomly divided in two groups. Maximum flow rate (Q max), duration of resection, weight of tissue resected, TUR syndrome, blood transfusion and duration of hospital stay and catheterization were compared in both groups. Results: There were 110 patients in both groups each. Post-operative Q max, duration of resection, weight of tissue resected, duration of hospital stay, duration of catheterization was statistically insignificant. While statistically significant difference was found only the duration of procedure. Conclusion: Bipolar and monopolar have the same clinical out-come and complication rates, yet the monopolar TURP requires significantly less operating time in comparison to bipolar TURP efficacy. Both procedures can be used for the treatment equally however if urologist want to save the time he should use monopolar TURP. Keywords: Monopolar TURP; Bipolar TURP; Enlarge Prostate